Swedish - Finnish glossary: the royal court - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary with word relating to the royal court. Published in Kieliviesti 2/2010. Contains approximately 140 entries. 2010.

Svensk-sverigefinsk ordlista med ord kring det kungliga hovet. Publicerades i Kieliviesti 2/2010. Innehåller ca 140 ord. 2010.
Svensk-finsk ordlista: kungliga hovet
Keywords: monarchy; monarki; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur